Solitary fibrous tumors: radiologic features with clinical and histopathologic correlation - Xiao, Ying; Chen, Jiaer; Yang, Wenbin; Yan, Hongfei; Chen, Ruowei; Li, Yangkang (Frontiers in Oncology, 2025)
ObjectiveSolitary fibrous tumor (SFT) is an uncommon mesenchymal neoplasm that exhibits a broad spectrum of biological behaviors. Few studies relative to clinical-pathologic features and radiologic manifestations of SFTs have been reported. This study aimed to correlate the radiologic findings of SFTs with the clinical and histopathologic features.MethodsThe clinical, surgical, and histopathologic records; and CT or MR images in 38 pathologically proved cases of SFTs were retrospectively evaluated.ResultsAll tumors were seen as oval (n=18) or irregular (n=20), well-defined (n=36) or ill-defined (n=2) masses with a mean size of 11.0 cm. On CT images, most tumors showed a heterogeneous density on precontrast image, and the mean density of the tumor parenchyma was 40.7 hounsfield units. Intratumoral calcification was seen in 6 tumors. After contrast media administration, most tumors showed moderate to marked enhancement (n=34). Multiple intratumoral vessels were seen in 23 tumors. Collateral feeding vessels were seen in 19 tumors. On MR images, all 6 tumors showed a low signal intensity on T1 weighted images and high signal intensity with separate foci of hypointensity on T2 weighted images, as well as significantly imhomogeneous enhancement after contrast administration.ConclusionThe presence of a large, well-defined, highly vascular soft tissue tumor with map-like enhancement and prominent collateral feeding vessels should alert the radiologist to the possible diagnosis of SFT. Diagnostic imaging coupled with clinicopathologic analysis allows accurate localization, identification, and resection of SFTs.